Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(42-x\right)\times8=264\)
\(\Leftrightarrow42-x=264\div8\)
\(\Leftrightarrow42-x=33\)
\(\Leftrightarrow x=42-33\)
\(\Leftrightarrow x=9\)
\(\left(x-46\right)\div8=33\)
\(\Leftrightarrow x-46=33\times8\)
\(\Leftrightarrow x-46=264\)
\(\Leftrightarrow x=264+46\)
\(\Leftrightarrow x=310\)
a,(42-x)*8=264
42-x =264:8
42-x =33
x =42-33
x =9
b,(x-46):8=33
x-46 =33*8
x-46 =264
x =264+46
x =310
a 180 -(x + 15) : 4 =80:5 180 - (x + 15) : 4 = 16 180 - ( x + 15) = 16 x 4 180 - ( x + 15 ) = 64 x + 15 = 180 - 64 x + 15 = 116 x= 116 - 15 x = 101
câu 9
6x(y + 9845)=174252
(y + 9845)=174252:6
(y + 9845)=29042
y=29042-9845
y=19197
Vậy y=19197
câu 9: 6.(y+9845)=29042.6
=>6.(y+9845)=174252
=>y+9845=174252:6
=>y+9845=29042
=>y=29042-9845
=>y=19197
Vậy y=19197
`yxx8 +yx2 =420`
`yxx(8+2)=420`
`yxx10=420`
`y=420:10`
`y=42`
y x ( 8 + 2 ) = 420
y x 10 = 420
y = 420 : 10
y = 42